JURIDICAL REVIEW OF MORTGAGE RIGHTS GUARANTEES IN CREDIT AGREEMENTS ACCORDING TO LAW NUMBER 4 OF 1996 CONCERNING MONITORING RIGHTS: - Henry Aspan; Rahmad Mirad; Ami Natuz Zahara (RADJA PUBLIKA, 2024)
Risks that generally occur in providing credit facilities are failure or delays in repayment of credit (credit risk), risks arising from market movements (market risk), risks due to the bank being unable to fulfill its maturing obligations (liquidity risk), and risks due to there are weaknesses in the juridical aspect caused by legal demands, the absence of supporting legislation (legal risks). In Article 1 number 11 of Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking, the definition of credit is formulated